Socio-Economic Analysis of the Resilience of Tobacco Farmers in Tatung Village in Maintaining Sustainable Agriculture - Irvan Nur Ridho; Bambang Triono; Dwiati Marsiwi; Nong Bang Nguyen (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
The dynamics of tobacco farmers’ economic livelihoods in Indonesia represent a crucial issue in terms of agricultural sustainability. The discourse surrounding tobacco farmers is full of pros and cons. On the one hand, tobacco farming contributes significantly to regional income; on the other hand, it poses challenges in the midst of smoking restrictions. Moreover, there is growing discourse on replacing natural tobacco with synthetic tobacco and even taro leaves as substitutes. This study employs a qualitative method with a phenomenological design, conducted in Tatung Village, Balong   District, Ponorogo Regency. Data were collected through direct observation, interviews, and documentation to capture how local farmers strategize in facing challenges that threaten the sustainability of tobacco farming. The resilience model of tobacco farmers can be formulated into three main pillars: individual capabilities, community social capital, and informal institutional support. These three pillars are interconnected and together form a strong socio-ecological foundation for coping with dynamic shifts in the economy, climate, and policy. The practical implications of this study are the need for agricultural policies that recognize local capacities and adaptive strategies of farmers, encourage the formation of community-based farmer cooperatives, increase farmers' access to market information and sustainable planting technologies. The resilience model found in this study can be replicated in other areas with similar agricultural commodities.Dinamika mata pencaharian ekonomi petani tembakau di Indonesia merupakan isu krusial dalam hal keberlanjutan pertanian. Wacana seputar petani tembakau penuh dengan pro dan kontra. Di satu sisi, pertanian tembakau berkontribusi secara signifikan terhadap pendapatan daerah; Di sisi lain, itu menimbulkan tantangan di tengah pembatasan merokok. Selain itu, ada wacana yang berkembang tentang penggantian tembakau alami dengan tembakau sintetis dan bahkan daun talas sebagai pengganti. Penelitian ini menggunakan metode kualitatif dengan desain fenomenologis, yang dilakukan di Desa Tatung, Kecamatan Balong, Kabupaten Ponorogo. Data dikumpulkan melalui observasi langsung, wawancara, dan dokumentasi untuk menangkap bagaimana petani lokal menyusun strategi dalam menghadapi tantangan yang mengancam keberlanjutan pertanian tembakau. Model ketahanan petani tembakau dapat dirumuskan menjadi tiga pilar utama: kemampuan individu, modal sosial masyarakat, dan dukungan kelembagaan informal. Ketiga pilar ini saling berhubungan dan bersama-sama membentuk fondasi sosial-ekologis yang kuat untuk mengatasi pergeseran dinamis dalam ekonomi, iklim, dan kebijakan. Implikasi praktis dari penelitian ini adalah perlunya kebijakan pertanian yang mengakui kapasitas lokal dan strategi adaptif petani, mendorong pembentukan koperasi tani berbasis masyarakat, meningkatkan akses petani terhadap informasi pasar dan teknologi penanaman berkelanjutan. Model ketahanan yang ditemukan dalam penelitian ini dapat direplikasi di daerah lain dengan komoditas pertanian serupa.